Photo-reduction enables catalyst regeneration in Fenton reaction on an Fe2O3-decorated TiO2 nanotube-based photocatalyst. Issue 20 (5th May 2020) - Peng, Quanming; Peng, Guiming; Wu, Liangpeng; Chen, Yaqian; Han, Bin; Su, Qiucheng; Liu, Shijun; Li, Xinjun
Abstract : Active Fe 2+ sites of TNT(Pd)/Fe2 O3 with a unique electronic structure for the Fenton reaction can be self-generated. Abstract : The Fenton reaction is regarded as an advanced oxidation process that can efficiently remediate environmental pollutants. However, the one-time irreversible consumption of its catalysts raises the cost in practical application. Herein, we report the generation of active Fe 2+ sites via photo-reduction by photogenerated electrons on a TiO2 nanotube-based catalyst (TNT(Pd)/Fe2 O3 ) with Fe2 O3 decorated on the outside wall, while the inside cavity entrapped Pd nanoparticles. Fenton catalytic investigations under visible light show that TNT(Pd)/Fe2 O3 displays superior methyl orange degradation activity with 90% removal in 10 minutes. The kinetic constant is 4.3 times as the sum of the pure photocatalysis and Fenton catalytic kinetic constants. The synergistic effect between the Fenton and photocatalytic reactions is further evidenced by the photocurrent and photodegradation tests. The TNT(Pd)/Fe2 O3 catalyst showed no decay in the Fenton-photocatalytic performance over three successive cycles. XPS measurements after long-term stability tests revealed no loss, but a slight increase in the number of Fe 2+ species. All of these results suggest that the most active Fe 2+ species in the Fenton reaction can be regenerated via the reduction by photogenerated electrons. This work addressed the challenge in catalyst regeneration in the traditional Fenton reaction via photoreduction by rational combination with a photocatalyst and the realized synergistic effect between photocatalysis and the Fenton reaction.